Characterization of the subventricular-thalamo-cortical circuit in the NP-C mouse brain, and new insights regarding treatment - Park, Min Hee; Choi, Byung Jo; Jeong, Min Seock; Lee, Ju Youn; Jung, In Kyung; Park, Kang Ho; Lee, Hye Won; Yamaguchi, Tomoyuki; Marti, Hugo; Lee, Beom Hee; Schuchman, Edward H.; Jin, Hee Kyung; et al. (Molecular therapy, 2019)
Gliosis in Niemann-Pick type C (NP-C) disease is characterized by marked changes in microglia and astrocytes. However, the gliosis onset and progression in NP-C has not been systematically studied, nor has the mechanism underlying this finding. Here, we found early gliosis in the subventricular zone (SVZ) of NP-C mice. Neural progenitor damage by Npc1 mutation suppressed vascular endothelial growth factor (VEGF) expression and further induced microglia activation followed by astrogliosis. Interestingly, excessive astrogliosis in the SVZ induced neural progenitor retention and/or migration into thalamus via astrocyte-derived VEGF, resulting in acceleration of thalamic and cortical gliosis through thalamo-cortical pathways. Transplantation of VEGF-overexpressing neural stem cells into the SVZ improved whole-brain pathology of NP-C mice. Overall, our data provide a new pathological perspective on NP-C neural pathology, revealing abnormalities in the subventricular-thalamo-cortical circuit of NP-C mouse brain and highlighting the importance of the SVZ microenvironment as a therapeutic target for NP-C disease.